Discovery of thymol-fused chalcones as new competitive \(α\)-glucosidase inhibitors: Design, synthesis, biological evaluation, and molecular modeling studies - Ade Danova; Elvira Hermawati; Warinthorn Chavasiri; Didin Mujahidin; Anita Alni; Robby Roswanda (Communications in Science and Technology)
This study aims to synthesize and evaluate the inhibitory activity of thymol derivatives targeting ?-glucosidase using in vitro and in silico studies. Ten thymol derivatives (2-11) including five new thymol-fused chalcones (7-11) were successfully synthesized. Among them, four compounds (4, 8, 9, 11) showed the best inhibitory activity with IC50 values of 18.45, 13.75, 8.86, and 10.67µM compared with acarbose (IC50 = 832.82 µM), respectively. The kinetic study of three new thymol-fused chalcones (8, 9, 11) exhibited a competitive inhibition. Molecular docking demonstrated the predicted interactions between ligand (8, 9, 11) and ?-glucosidase, which are responsible for inhibiting the enzyme's catalytic abilities. Furthermore, molecular dynamics simulation of the enzyme-ligand 9 complex indicated that this complex was stable in aqueous condition. This research contributes significantly to the understanding of thymol-fused chalcones that may have therapeutic potential and their possible application in the treatment of type 2 diabetes mellitus (T2DM) for further study.